Experimental Investigation of the Permeability Measurement of Radial Flow through a Single Rough Fracture under Shearing Action - Ran Tan; Junrui Chai; Cheng Cao (Advances in Civil Engineering)
Water flow is commonly observed in rock fractures, and this flow has considerable significance in many aspects of rock engineering. In this study, seepage-stress coupled tests were performed on fractured rock masses using a computer-controlled direct shear device for rock with seepage control. The flow direction was radial. Eight types of test case were designed, and subgroup tests with varied normal stress, shear velocity, and roughness of fracture surface were conducted. The failure state of the fracture surface after the shear test, changes in shear stress, and fissure width and permeability under the above conditions were analyzed. The results include the following: the grain size of gouge fragments produced in rough fracture decreased with an increase in normal stress during shearing; the grain size of gouge fragments affected the fracture permeability; and the influence of shear velocity on the test results was mainly reflected after the peak strength. Additionally, a new expression describing fluid flow through fracture gouge is proposed.